The Effect of Strengthening Ball Roll Exercise and Strengthening Heel Raises Exercise On Static Balance In Children With Flat Foot In Sragi Subdistrict - Nurul Aktifah (P3M Universitas 'Aisyiyah Surakarta, 2021)
The arch of a foot that is not formed normally is called a Flat foot. Flat foot can cause balance disorders in children. How to improve static balance can be done with strengthening ball roll exercise and strengthening heel raises exercise.The purpose of this study was to determine the effects of strengthening ball roll exercise and strengthening heel raises exercise on static balance in children’s flat foot at Sragi District.This study using quasi experimental design (non randomized control group pretest posttest design) consists of two groups, in control group consisted of 24 respondents, and in experiment group there are 24 respondents. The results of Wilcoxon test in control group showed p>0,05 and p value in experiments group is p<0,05, it means there is an effect of strengthening ball roll exercise and strengthening heel raises exercise on respondents’s static balance. The Mann Whitney U test, which was used as a defference test, obtained p = 0.443 on the right foot and p = 0.000 on the left foot. It means that was difference in the effectiveness of strengthening ball roll exercise and strengthening heel raises exercise on static balance in experiments group compared to the control group.